Dosage of heparin for patency of the totally implanted central venous catheter in cancer patients - de Oliveira, Francisca Jane Gomes (Rev Lat Am Enfermagem, 2020)
OBJECTIVE: to analyze the evidence available in the literature about the lowest necessary dose of heparin to maintain the patency of the totally implanted central venous catheter in adult cancer patients. METHOD: an integrative literature review, carried out in the following databases: Literatura Latino-Americana e do Caribe em Ciências de Saúde, Sciverse Scopus, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Cochrane Central Register of Controlled Trials, including thirteen studies. RESULTS: the evidence showed that the dose of heparin (300 IU/ml) is the most used in maintaining the patency of the totally implanted central venous catheter. CONCLUSION: according to the selected studies, the lowest dose of heparin found in maintaining the patency of the totally implanted central venous catheter in cancer patients was 10 UN/ml with a volume of 5 ml of the heparin solution.